2013
DOI: 10.4149/bll_2013_106
|View full text |Cite
|
Sign up to set email alerts
|

Preeclamptic cord blood hemolysis and the effect of Monascus purpureus and Saccharomyces cerevisiae in modulating preeclamptic stress

Abstract: Abstract:Background: Preeclampsia is associated with impaired antioxidant defense that results in maternofetal complications. In addition to antioxidant defi ciency, hemolytic disorder has also been observed in preeclamptic mother.Methods: This study aims in analyzing the fetal complications using cord blood RBC (red blood cell); further the antihemolytic and antioxidant effi ciency of two common probiotic yeasts Monascus purpureus and Saccharomyces cerevisiae in preeclamptic and normotensive RBCs were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…80 Therefore, the physiologic consequences of PEC extend beyond the maternal environment and contribute to fetal complications. A study by Ekambaram et al 37 investigated the antihemolytic and antioxidant efficiency of two probiotic yeasts ( Monascus purpureus and Saccharomyces cerevisiae ) on fetal cord blood red blood cells (RBC) of infants born to PEC mothers as compared to healthy normotensive controls. The red blood cells of the PEC sample were found to have low anti-oxidant status ( P <0.05), increased oxidative stress, ( P <0.05), increased nitrative stress ( P <0.05), and increased hemolysis ( P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…80 Therefore, the physiologic consequences of PEC extend beyond the maternal environment and contribute to fetal complications. A study by Ekambaram et al 37 investigated the antihemolytic and antioxidant efficiency of two probiotic yeasts ( Monascus purpureus and Saccharomyces cerevisiae ) on fetal cord blood red blood cells (RBC) of infants born to PEC mothers as compared to healthy normotensive controls. The red blood cells of the PEC sample were found to have low anti-oxidant status ( P <0.05), increased oxidative stress, ( P <0.05), increased nitrative stress ( P <0.05), and increased hemolysis ( P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Ekambaram et al demonstrated that a diet rich in yeast species Monascus purpureus and Saccharomyces cerevisiae could serve as a good natural antioxidant source and probiotic supplement to alleviate the stress status of preeclamptic patients and their babies. They had significant catalase activity, inhibited formation of lipid peroxide and nitrite/nitrate in cord blood red blood count of preeclamptic and normotensive subjects [91].…”
Section: Probiotics/prebioticsmentioning
confidence: 97%